Edukasi Senam Rematik untuk Mengatasi Kekakuan Sendi dengan Terapi Non-Farmakologis di Kelurahan Timbangan Ogan Ilir Palembang - Rosmiarti, Rosmiarti; Wiratama, Alprian; Anggela, Putri; Efendi, Siti Hartini; Nadian, Tria; Iskandar, Shahkila Nadira; Artati, Talitha; Susanti , Susanti; Faraqueen, Nazilla; Wulandari, Putri; Saputra, Ahmad Fadli (Jurnal Nusantara Mengabdi, 2024)
Purpose: This community service activity aims to introduce rheumatic exercises to the public who experience joint stiffness so that they can perform these exercises independently at home to prevent further joint stiffness through non-pharmacological therapy. Methodology: The method used in this activity provides education on rheumatic exercises with non-pharmacological therapy. The material was delivered using a lecture and Q&A method, while rheumatic exercises were demonstrated and practiced through demonstrations and simulations. The target group for this activity consisted of individuals over 40 years old suffering from joint stiffness in the Timbangan subdistrict of Ogan Ilir, Palembang, totaling 20 participants. Results: The results showed an increase in knowledge and skills regarding rheumatic exercises, especially for those suffering from joint stiffness, and for the public of Timbangan subdistrict in general. Counseling is used as a service activity, with health promotion media in the form of leaflets that include illustrated exercise instructions. Limitations: This activity was only conducted in Timbangan Village, Ogan Ilir, and Palembang, so its benefits have not yet been felt by people in other areas with similar conditions. The time for educating and assisting with rheumatic exercises was relatively limited, so long-term changes in participants’ habits could not be ensured. Contribution: This program promotes a healthy lifestyle by providing early prevention solutions for joint disorders, thus reducing reliance on medication. The program also helps increase public understanding of the importance of non-pharmacological therapy, particularly rheumatic exercises, as an alternative to overcome joint stiffness.